Evaluating sarcopenia prevalence and relationship with disease activity of primary Sjögren syndrome in females - Başaran, Pınar Özge; Eker Büyükşireci, Dilek (Universa Medicina, 2024)
BackgroundPrimary Sjögren’s syndrome (pSS) leads to impaired muscle function and mass as well as pain and fatigue. Sarcopenia is the pathological reduction of skeletal muscle mass and strength. We aimed to investigate the prevalence of sarcopenia and determine its relationship with disease activity levels in females with primary Sjögren syndrome. MethodsThis cross-sectional study was performed on 62 female patients diagnosed with pSS and 62 female age matched healthy controls. Disease activity was evaluated with the EULAR Sjögren’s syndrome patient reported index (ESSPRI) and EULAR Sjögren’s syndrome disease activity index (ESSDAI), fatigue severity scale (FSS), hospital anxiety and depression scale (HADS), and numerical rating scale (NRS). A simple questionnaire to rapidly diagnose sarcopenia (SARC-F) was used to screen for sarcopenia. Degree of sarcopenia was evaluated by handgrip strength, anterior thigh muscle thickness by USG, the 6-meter walk test (6MWT), and the five times sit-to-stand test (FTSST). ResultsThe prevalence of sarcopenia was found to be 36/62 (58.1%) in pSS and 6/62 (9.7%) in healthy controls (p<0.001). HADS anxiety and depression scores and SARC-F scores were significantly higher in pSS (p<0.001). There were significant differences in 6MWT, FTSST, and hand grip strength results in pSS (p<0.001). Anterior thigh muscle thickness was similar in both groups (p=0.298). A positive correlation was found between SARC-F on the one hand and ESSPRI and NRS on the other (r=0.595, p=0.009; r=0.569, p=0.014). ConclusionSarcopenia prevalence was increased in female patients with pSS and there was a relationship of SARC-F scores with pain and disease activity levels.